Modeling global habitat suitability and environmental predictor of distribution of a Near Threatened avian scavenger at a high spatial resolution - Yousefi, Masoud; Mohammadi, Saeed; Kafash, Anooshe (Frontiers in Ecology and Evolution, 2023)
Vultures are among the most vulnerable birds in the world. Bearded vulture (Gypaetus barbatus) is among the threatened species of vultures and listed as Near Threatened. The species is widely distributed across the Palearctic, Afrotropical and Indomalayan regions. The species faces several threats like poisoning, direct persecution, habitat degradation and collisions with powerlines and wind power farms. Thus knowing the species global habitat suitability and environmental predictors of the species distribution can facilitate the species conservation. In this study we applied maximum entropy approach, 10,585 distribution records and 10 environmental variables to model the bearded vulture global habitat suitability at high spatial resolution (30-arc-second (1 kilometer)). We also estimated protected areas coverage for the species suitable habitats. We identified 8,117,231 km2 of suitable habitat for the species across its global range in Europe, Asia and Africa. Results showed that topographic diversity is the most important predictor of the species distribution across its distribution range. Results of estimating area of suitable habitats of the bearded vulture within protected areas revealed that only 16.26% of the species suitable habitats are protected. The areas that identified to have highest suitability have high priority for conservation of this iconic species.